2018
DOI: 10.1093/gbe/evy085
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Patterns of Genomic Diversity Reveal Accelerated Genetic Drift but Reduced Directional Selection on X-Chromosome in Wild and Domestic Sheep Species

Abstract: Analyses of genomic diversity along the X chromosome and of its correlation with autosomal diversity can facilitate understanding of evolutionary forces in shaping sex-linked genomic architecture. Strong selective sweeps and accelerated genetic drift on the X-chromosome have been inferred in primates and other model species, but no such insight has yet been gained in domestic animals compared with their wild relatives. Here, we analyzed X-chromosome variability in a large ovine data set, including a BeadChip a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…Using this Felis_catus_9.0 assembly, a vast new repertoire of SNVs and SVs were discovered for the domestic cat. The total number of variants discovered across our diverse collection of domestic cats was substantially higher than previous studies in other mammals, such as, cow [ 38 ], dog [ 39 ], rat [ 40 42 ], sheep [ 43 , 44 ], pig [ 45 ], and horse [ 46 ]. Even rhesus macaques, with twice as many variants as human, do not approach the same levels of cat SNV variation [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Using this Felis_catus_9.0 assembly, a vast new repertoire of SNVs and SVs were discovered for the domestic cat. The total number of variants discovered across our diverse collection of domestic cats was substantially higher than previous studies in other mammals, such as, cow [ 38 ], dog [ 39 ], rat [ 40 42 ], sheep [ 43 , 44 ], pig [ 45 ], and horse [ 46 ]. Even rhesus macaques, with twice as many variants as human, do not approach the same levels of cat SNV variation [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 75%
“…For example, 36% of variants in an Icelandic population of over 2000 individuals had a minor allele frequency below 0.1% [59]. Similarly sized analyses in other mammals reported~20% of variants had allele frequencies < 1% [44,46,48]. As the number of cats sequenced increases, the resolution to detect rare variants, as well as the total fraction of low frequency variants, will continue to grow linearly as each individual will contribute a small number of previously undiscovered variants [60].…”
Section: Plos Geneticsmentioning
confidence: 97%
“…A study also used ROH to compare and characterize beef and dairy cattle breeds [ 14 ]. ROHs are also common in regions under positive selection and as such studies have associated accumulation of ROHs at specific loci to directional selection [ 13 , 15 ]. In a number of studies, ROH have been used to estimate inbreeding levels and infer on signatures of selection and genetic adaptation to production conditions [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the largest 40 Mb recombination coldspot in the center of chrX preserves independent signals of putative selective sweeps, with nearly identical, orthologous breakpoints in Panthera and in pigs (Ai et al 2015;Li, Davis, et al 2016;Figueiró et al 2017). This large region also largely overlaps syntenic segments in primates marked by selective sweeps, and extended regions of strong genetic differentiation between subspecies and species of rabbits and sheep with similar boundaries (Carneiro et al 2010;Carneiro et al 2014;Chen et al 2018) Nam et al 2015). A previous study also found that the same recombination coldspot was among the most strongly differentiated genomic regions distinguishing domestic cats from their wild progenitors (Montague et al 2014).…”
Section: Discussionmentioning
confidence: 94%